A Heat‐Activated Drug‐Delivery Platform Based on Phosphatidyl‐(oligo)‐glycerol Nanocarrier for Effective Cancer Treatment. Issue 6 (19th June 2021) - Hossann, Martin; Hirschberger, Johannes; Schmidt, Rebecca; Baumgartner, Christine; Zimmermann, Katja; Baer, Silke; Ratzlaff, Christina; Peller, Michael; Troedson, Karin; Limmer, Simone; Brühschwein, Andreas; Dörfelt, Rene; et al.
Abstract : Drug Delivery Doxorubicin‐loaded DPPG2 ‐TSL nanocarriers represent a novel temperature‐dependent drug delivery system. Heating the tumor tissue to 41°C leads to its intravascular doxorubicin release, which then penetrates the tumor tissue and results in significantly higher intratumoral doxorubicin concentrations. This improves local efficacy while reducing systemic side effects. The described nanocarriers have great potential for the treatment of locally advanced tumors in humans. More details can be found in article number 2000089 by Lars H. Lindner and co‐workers.